Perbedaan asupan mikronutrien pada lansia penderita hipertensi esensial yang overweight dan tidak overweight - Catur Saptaning Wilujeng; Wasilah Rochmah; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Hypertension in overweight elderly is a crucial problem considering that its pathogenesis, disease pattern and management are not entirely the same with hypertension in young adults. Hypertension in overweight elderly requires particular attention because it is closely associated with overall management (medical and nutritional).Objective: To study different intake of micronutrients, i.e. natrium (Na), potassium (K), calcium (Ca), and magnesium (Mg) in overweight and non overweight elderly with essential hypertension at Griya Sehat Lansia (GSL) Yogyakarta.Method: The study was analytical with case control study design. Samples were as many as 138 elderly of 60-75 years old taken using multistage sampling technique. Data of intake Na, K, Ca, Mg were obtained through semi quantitative food frequency questionnaire (FFQ); essential hypertension through assessment of blood pressure using sphygmomanometer; overweight and non overweight status through body mass index (BMI), BMI for overweight was 23-24.9 kg/m2 and non-overweight was 18.50-22.99 kg/m2. Statistical analysis used paired t test, Chi-Square and logistic regression.Results: There were differences in intake of Na, K, Ca, and Mg between overweight and non overweight elderly (p<0.05). There were significant association (p<0.05) between intake of Na, K, Ca, and Mg of overweight and non overweight elderly with essential hypertension, with OR 5.271; 6.813; 3.398 and 3.444. Intake of Na and K were variables most significantly associated with overweight and non overweight elderly with essential hypertension (p<0.05).Conclusion: There were significant differences in intake of micronutrients (Na, K, Ca, Mg) between overweight and non overweight elderly with essential hypertension at GSL Yogyakarta.